Interpretation of “Nushūz” (An-Nisa: 34) in the Digital Age: Cyber ​​Violence and the Redefinition of Marital Disobedience - Wilnan Fatahillah; Dedi Uska; Hari Winarsa; Untung Famuji (Al Qodiri : Jurnal Pendidikan, Sosial dan Keagamaan, 2026)
This study reinterprets the Qur’anic concept of nushūz in Qur’an 4:34 within the context of cyber violence and digitally mediated marital harm. Classical interpretations have often confined nushūz to physical departure, sexual refusal, or one-sided marital disobedience, thereby limiting its capacity to address non-physical forms of domination in contemporary Muslim households. Using qualitative conceptual research based on systematic library study, critical contextual hermeneutics, and feminist legal hermeneutics, this article examines selected tafsir works, Islamic family-law scholarship, and recent studies on technology-facilitated abuse. This study fills the gap between cyber-violence scholarship and Islamic legal hermeneutics by showing how digital abuse can be interpreted through Qur’anic marital ethics. The analysis demonstrates that nushūz contains a broader ethical meaning related to rupture, imbalance, arrogance, and serious relational disruption. When placed in dialogue with digital realities, cyber violence emerges as a form of marital harm that threatens privacy, dignity, psychological safety, autonomy, and relational justice. The study identifies three principal mechanisms of cyber-nushūz: extractive surveillance, including spyware and unauthorized tracking; reputational weaponization, including online humiliation and image-based abuse; and algorithmic restriction, including digital financial control and blocked access to communication technologies. The article contributes to contemporary Islamic family law by proposing cyber-nushūz as a legal-ethical category grounded in Qur’anic ethics and maqāṣid al-sharī‘ah. This framework expands the interpretation of nushūz beyond bodily and spatial disobedience toward a digital rights-based understanding of marital violation. Practically, the findings offer a normative basis for religious courts, mediators, and Muslim family-law practitioners to recognize coercive digital conduct as serious marital harm in digitally connected societies.